2012
DOI: 10.1007/s00396-012-2631-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thermal stability of polypropylene using DOPO-immobilized silica nanoparticles

Abstract: After the surface silylation with 3-methacryloxypropyltrimethoxysilane, silica nanoparticles were further modified by 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). The immobilization of DOPO on silica nanoparticles was confirmed by Fourier transform infrared spectroscopy, UV–visible spectroscopy, magic angle spinning nuclear magnetic resonance, and thermogravimetric analysis. By incorporating the DOPO-immobilized silica nanoparticles (5 wt%) into polypropylene matrix, the thermal oxidative stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Some studies have shown the interest of the surface modification of silica by DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) compared with the simultaneous addition of silica and DOPO on thermal stability of PP [34]. Dong et al pointed out the synergistic effect of 3.2 wt% of DOPO immobilized on silica nanoparticles (5 wt% in PP) with an enhancement of the thermal stability of 90 C under air.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have shown the interest of the surface modification of silica by DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) compared with the simultaneous addition of silica and DOPO on thermal stability of PP [34]. Dong et al pointed out the synergistic effect of 3.2 wt% of DOPO immobilized on silica nanoparticles (5 wt% in PP) with an enhancement of the thermal stability of 90 C under air.…”
Section: Introductionmentioning
confidence: 98%
“…Presence of hydroxyl groups on the surface of SiO 2 NPs and high surface area cause silica aggregates [18]. Double layer surface modification of SiO 2 NPs with CA as the first layer and AA as the second is a novel method and it can prevent the SiO 2 NPs from aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [20] reported that nanosilica reacted with the reactive antioxidant via transesterification to form a nanosilica hybrid material, the nanosilica-immobilized antioxidant was homogeneously dispersed into the matrix and the aging-resistance ability of polypropylene was improved. Dong et al [21] prepared 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)-immobilized silica nanoparticles, which could improve the dispersion of inorganic nanoparticles and the thermal stability of iPP. Tang et al [9] described that with the addition of zinc oxide nanoparticles coated with organic nucleating agents, the crystallization temperature of iPP increased by an additional 7 ° C relative to iPP, with only organic nucleating agents and nonspherulitic birefringent textures in iPP were observed.…”
Section: Introductionmentioning
confidence: 99%